Pengaruh Time Token Learning Literasi Sains terhadap Keterampilan Komunikasi dan Hasil Belajar Kognitif Peserta Didik SMPN XYZ - Verlia Agustin S; Neng Sholihat; Berry Kurnia Vilmala (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
This study aims to determine the influence of the Time Token Learning Type learning model combined with science literacy on communication skills and cognitive learning outcomes of SMPN XYZ students. The background of this research is low communication skills and student learning outcomes that are still substandard, so an innovative learning approach is needed that can improve both aspects. The research method used was quasi experimental with a Pretest-Posttest Control Group Design. The research subjects involved one experimental class given Time Token Learning type learning with science literacy content and one control class that used conventional learning. The research instrument consisted of a reasoned multiple-choice test to measure cognitive learning outcomes and an observation sheet to assess communication skills. The results of the study show that the application of the Time Token Learning model with science literacy has a significant influence on improving students' cognitive learning outcomes. The average pretest score of 40 increased to 75 in the posttest with an N-Gain value of 45.5% which was in the medium category. These findings prove that the learning model is effective in improving students' understanding of concepts and cognitive thinking skills. However, the results of the analysis of communication skills did not show a significant improvement. In addition, the correlation between communication skills and learning outcomes was also insignificant with a significance value of 0.826 > 0.05. In conclusion, the Time Token Learning model with science literacy has proven to be effective in improving students' cognitive learning outcomes, but has not been able to optimally develop communication skills. Therefore, it is necessary to develop additional strategies or a combination of other learning models so that communication skills can develop in line with improving cognitive learning outcomes.